Fault-tolerant model predictive control of a direct methanol-fuel cell system with actuator faults. (September 2017) - Keller, R.; Ding, S.X.; Müller, M.; Stolten, D.
Abstract: This paper investigates fault tolerant model predictive control (MPC) of a direct methanol fuel cell (DMFC) system with several faults in the methanol feeding pump. An active FTMPC strategy with a hierarchal structural design is developed. The focus here is on fault detection and isolation (FDI) and the implementation of fault-tolerant strategies within the control algorithm. To this end, a model-based FDI scheme with virtual sensors is first developed by means of the real-time diagnosis of fault occurrence during operation. Thereby, several faults in the methanol pump are characterized and the information integrated into the MPC algorithm in each fault case. Strategies are presented to reconfigure the active fault-tolerant MPC to keep the DMFC system stable in case of a feeding failure. Moreover, economic, stability and lifetime characteristics are also integrated into the active fault-tolerant MPC. The proposed FDI and FTMPC scheme is tested experimentally in a DMFC test rig with a 5-cell DMFC stack to demonstrate the effectiveness and robustness of the designed approach. Several fault scenarios with the FTMPC are shown. Particularly in the case of fuel cells, fault tolerance is necessary to meet the goals of long-lasting system stability and efficiency. Highlights: Model predictive control with successive linearization of a DMFC system. Two virtual sensors estimate the methanol flow integrated in the FDI. Fault tolerance within four fault scenarios of the methanol pump. Fuel economy and system efficiency implemented in the fault tolerant structure. Experimental results demonstrate the effectiveness and robustness of the designed approach.